خویندنه وه یه کی سوسیولوژیانه بو چه مکی گه نج شیکردنه وه یه کی تیوری شیکارییه تویژینه وه یه کی مه یدانییه له شاری هه له بجه - حسێن, پ.ی.د. توانا فەرەیدون; عبدالله, مظفر جبار (Sulaimani Journal for Humanities, 2023)
The significance of young people in society cannot be overstated, as they play a crucial role in the development and progress of any modern and advanced community. To gain comprehensive insights into this demographic, extensive scientific research becomes imperative. This study represents a sincere endeavor to explore the concept of youth through a sociological lens, steering away from merely artistic or historical interpretations. Instead, it delves into a meticulous examination and analysis of various facets of youth. The research commences by adhering to the fundamental principles of scientific inquiry, elucidating the research's problems, significance, and objectives. Subsequently, the study delves into the origins of adolescence, offering diverse perspectives on the matter. To provide the reader with a deeper understanding of adolescence's essence, developmental psychologists, biologists, and especially sociologists' viewpoints are thoroughly explored, with particular emphasis on the latter due to its pertinence to the research. To ensure accuracy and up-to-dateness, the study relies on the most recent and reliable sources for each subject covered.